Cadmium response of the hairy root culture of the endangered species Adenophora lobophylla - Wu, S (Plant science : an international journal of experimental plant biology, 2001)
We generated hairy root cultures from two closely related species, Adenophora lobophylla and A. potaninii (Campanulaeae) and carried out a comparative study on their cadmium (Cd) response. A. lobophylla is an endangered species while A. potaninii is widely distributed in the same habitat. Upon exposure to Cd concentrations higher than 50 µM, more extensive growth inhibition and higher Cd accumulation were detected in the hairy root of A. lobophylla. Cd treatment affected the protein content in both the species. Phytochelatins (PCs) have been isolated and characterized from the hairy roots for both species. They shared structure similarities but showed different accumulation kinetics. The content of reduced glutathione (GSH) and cysteine (Cys) differs in both the species and they show different changes upon Cd challenge. The results suggested that these two species might employ different strategy for Cd detoxification. A. lobophylla is capable of synthesizing high level of PCs while a Cd exclusion system and a tighter homeostasis mechanism(s) to maintain the cellular GSH level could have been evolved in A. potanini in additon to its capability of synthesizing PCs